МАТЕМАТИЧНЕ МОДЕЛЮВАННЯ ТА РЕГУЛЮВАННЯ ПРОЦЕСІВ КОМПЛЕКСНОЇ ЕЛЕКТРОТЕРМООБРОБКИ АЛЮМІНІЄВОЇ ЖИЛИ СИЛОВОГО КАБЕЛЮ - О.Д. Подольцев; А.А. Щерба; В.В. Золотарьов; Р.В. Білянін; М.А. Кулик (Праці Інституту електродинаміки Національної академії наук України, 2022)
In the work using the finite element method, a three-dimensional computer model of the processes of electrothermal treatment of an aluminium core of a power cable in an electric furnace and a thermostat was developed, and the patterns of changes in the temperature field in such a core were determined under different modes of implementation of the so-called "annealing" processes, that is, the restoration of the necessary electrical properties in it , in particular, an increase in specific electrical conductivity and plasticity. Calculations based on the developed mathematical model and the obtained regularities are consistent with the results of practical measurements of electrical conductivity and plasticity of experimental samples of aluminium cores of cables manufactured by YUZHCABLE WORKS, PJSC, Kharkiv. However, the analysis of the patterns of changes in the temperature field in the volume of aluminium cores of cables during their continuous electric heating to the required temperatures of both the outer and inner layers of the core wound on a spool showed that the difference in their temperatures can exceed 50 0С. Such nonuniformity of the temperature field of the core and long-term overheating of its outer layers leads to unacceptable losses of electricity and reduces the positive result of the processes of such heat treatment of the core, in particular, regarding the increase of its electrical conductivity. It is substantiated that in order to reduce the loss of electricity and the nonuniformity of the temperature field in the aluminium core, it is necessary to reduce the duration of electric heating of the aluminium core to the temperature of its upper layers, necessary for annealing, and then move the drum with such a core to a thermostat without electronic heating elements. In such a thermostat, the temperature of the outer layers will decrease, and the temperature of the inner layers will continue to increase. The work shows that after some time (≈ 60 min), the temperature distribution in the core will become almost uniform, and the total losses of electricity and the nonuniformity of the temperature field in the volume of the core will become smaller. Based on the results of the calculations, recommendations were developed for the selection of appropriate modes of heat treatment of aluminium cores wound on a spool, with acceptable energy consumption and overheating of the upper layers of the core.